Syphilis in female sex workers: an epidemiological study of the highway system of the state of Pará, northern Brazil - Natalia dos Santos Cavalcante (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: Female sex workers (FSWs) are considered a bridge for transmission of pathogens from high-risk to general populations. We assessed the epidemiological status of syphilis in FSWs along the Pará highway system. METHODS: Two hundred and twenty-two FSWs were interviewed and samples were analyzed using rapid qualitative tests and real-time polymerase chain reaction. RESULTS: The prevalence of syphilis was high (36.94%). The high rate of prostitution, use of illicit drugs, and search for financial resources increased Treponema pallidum transmission through unprotected sex. CONCLUSIONS: Several characteristics of FSWs were identified, which reinforce the need for measures guaranteeing their health and protection.